One Dimensional Inorganic Oxovanadium Polymers Functionalized with Manganese(Ii) Complexes: Structural and Magnetic Characterization - Venegas-Yazigi, D; Venegas-Yazigi, D (2012)
Two organo-inorganic hybrid manganese(II) vanadates [Mn(phen) 2(VO 3) 2] ? (1) and [{Mn(bipy)(VO 3) 2}{VO 2(bipy)}(VO 3)(V 2O 6)] ? (2) were synthesized hydrothermally. Compound 1 is a chain consisting in VO 3 units propagating along the b axis, decorated with {Mn(phen) 2} +2 subunits. Compound 2 is a ladder like structure propagating along the a axis, consisting of two helical chains connected by the heterobinuclear {Mn(bipy)VO 4 (2,2?-bipy)} moieties, generating a double helical structure. Magnetization measurements reveal that dominant antiferromagnetic interactions are mediated between the manganese(II) centers for both structures through oxovanadate bridges. Magnetic data of compound 1 were fitted with the analytical expression for a regular chain model, estimating a J value of -0.30 cm -1. The DAVE code was use to fit experimental data and calculate the values of the super exchange constants for 2, assuming four different exchange pathways, J 12 = -0.17 cm -1; J 23 = -0.12 cm -1; J 13 = -0.08 cm -1; J 24 = -0.05 cm -1. DFT calculations on a tetranuclear fragment of 2, using diamagnetic substitutions, gave super exchange values of J 12 = -17.5 cm -1 and J 23 = -8.5 cm -1, corroborating the antiferromagnetic nature of the interactions as observed experimentally. © 2012 Elsevier Ltd. All rights reserved.